Pengaruh Motivasi dan Pelatihan terhadap Kinerja Pegawai dengan Budaya Kerja sebagai Variabel Intervening - Ena Marliana; Dedi Kusmayadi; Edy Suroso (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This research aims to examine the influence of motivation and training on performance with work culture as an intervening variable. The study was conducted on Civil Servants in General Functional Positions and Certain Functional Positions in the City of Tasikmalaya. Sampling was carried out using techniques proportionate stratified random sampling, with a total sample size of 374 samples, in 37 regional apparatus organizations in Tasikmalaya City. The research instrument used was a questionnaire with scale likert. The analysis technique used is path analysis using the SPSS application. The results of this research show that 1) Motivation, Training and Performance are in good condition. Meanwhile the Work Culture is in Very Good Condition; 2) Motivation has a positive and significant effect on work culture; 3) Training has a positive and significant effect on work culture; 4) Motivation has a positive and significant effect on performance; 5) Training has a positive and significant effect on performance; 6) Work culture has a positive and significant effect on performance; 7) Motivation and training have a positive effect on work culture; 8) Motivation, training and work culture have a positive effect on performance.